Hyperandrogenism in women : beyond polycystic ovary syndrome - Pasquali, Renato; Pignatelli, Duarte (Frontiers of hormone research / series editor Ezio Ghigo, 2019)
Hyperandrogenism profoundly affects women's lives from lowering self-esteem to changing cognition and affective motivation. The polycystic ovary syndrome (PCOS) is the most common androgen excess disorder worldwide. While it is not the focus of this book, some aspects are discussed. The aim of this book is to improve understanding of androgen excess and its impact on several conditions. Topics include development of adipose tissue in females, insulin sensitivity, congenital adrenal hyperplasia, and Cushing's disease/syndrome. There is also a discussion of PCOS with emphasis on in utero origins and specific genetic and epigenetic factors. This book provides a wealth of relevant information for every endocrinologist and gynecologist who wants to broaden their knowledge of androgens in various conditions.